Feasibility of Barley Straw Fibers as Reinforcement in Fully Biobased Polyethylene Composites: Macro and Micro Mechanics of the Flexural Strength - Ferran Serra-Parareda; Fernando Julián; Eduardo Espinosa; Alejandro Rodríguez; Francesc X. Espinach; Fabiola Vilaseca (Molecules, 2020)
Awareness on deforestation, forest degradation, and its impact on biodiversity and global warming, is giving rise to the use of alternative fiber sources in replacement of wood feedstock for some applications such as composite materials and energy production. In this category, barley straw is an important agricultural crop, due to its abundance and availability. In the current investigation, the residue was submitted to thermomechanical process for fiber extraction and individualization. The high content of holocellulose combined with their relatively high aspect ratio inspires the potential use of these fibers as reinforcement in plastic composites. Therefore, fully biobased composites were fabricated using barley fibers and a biobased polyethylene (BioPE) as polymer matrix. BioPE is completely biobased and 100% recyclable. As for material performance, the flexural properties of the materials were studied. A good dispersion of the reinforcement inside the plastic was achieved contributing to the elevate increments in the flexural strength. At a 45 wt.% of reinforcement, an increment in the flexural strength of about 147% was attained. The mean contribution of the fibers to the flexural strength was assessed by means of a fiber flexural strength factor, reaching a value of 91.4. The micromechanical analysis allowed the prediction of the intrinsic flexural strength of the fibers, arriving up to around 700 MPa, and coupling factors between 0.18 and 0.19, which are in line with other natural fiber composites. Overall, the investigation brightness on the potential use of barley straw residues as reinforcement in fully biobased polymer composites.